A főnix újjászületése Petrarca Daloskönyvében - Vígh, Éva (Antikvitás & Reneszánsz, 2018)
In the history of civilization and ancient literature, from Hesiod, Herodotus, Pliny, Tacito, Ovid to early Christian authors the symbolism of the bird periodically reborn from its ashes continued to survive in the sheets of encyclopedias and bestiaries. The image of the phoenix was transmitted by medieval troubadour poetry in form of rhetorical figures. Francesco Petrarca was not only the renewer of European poetry: he opened a completely singular way even in the interpretation of the unica avis. After having briefly outlined the poetic and spiritual symbolism of the phoenix, the paper focuses on a new poetic role of the bird present in six poems of Canzoniere, accentuating its reflective and pondered contiguousness.